Characterisation and differentiation potential of rat full-term amniotic fluid stem cells into the derivatives of the three primary germ layers - Hoo, Mun Fun (2015)
Amniotic fluid (AF) is believed to contain highly potent stem cells which make them a reliable source for stem cells with wider differentiation spectrum. However, very few studies have established amniotic fluid stem cells (AFSCs) from full-term AF as most AFSCs were established from mid-term AF. Here, the study aimed to see if rat full-term AF harbours such stem cells with differentiation potential not only into derivatives of the three primary germ layers but also the functional ones. Isolation of amniotic fluid stem cells (AFSCs) from rat full-term AF was carried out using immuno-selection (miniMACS) against c-kit, a stem cell factor receptor that is expressed during embryogenesis. The requirement of leukaemia inhibitory factor (LIF) to maintain the differentiation potential of c-kit positive cells was investigated as part of the cell culture condition optimization. The cells were then characterized with population doubling time, panels of pluripotency and stemness markers and spontaneous differentiation capacity by assessing their ability to form good quality multicellular aggregates, embryoid bodies (EBs). The ability of the cells to undergo directed differentiation into the derivatives of the three primary germ layers, specifically the ectodermal (neurons and glial cells), mesodermal (cardiomyocytes, adipocytes and osteocytes) and endodermal (insulin secreting pancreatic β-cells) cells, as well as their functionality were then studied. Monolayer differentiation protocol was used for neural differentiation where the differentiated cells were analysed with specific markers for early (Pax6 and Nestin), post-mitotic (Class III β-tubulin) and mature neuronal markers (Calbindin, MAP2, GFAP, TH and Synaptophysin). For mesodermal differentiation, retinoic acid (RA), 5-Azacytidine C (5-Aza) and Vitamin C (Vc) treatments were applied prior to re-plating the EBs at high density. The cells were then subjected to O-Red oil (fat), Alizarin Red (bone), Alcian Blue (cartilage) staining and mature cardiac markers analysis (cardiac troponin, SERCA and GATA6). For endodermal differentiation, cells were sequentially treated with Activin A, Wnt3a, FGF7, Cyclopamine and retinoic acid before being analysed with pancreatic markers (brachyury, PDX1, CXCR4, NKX 6.1, HNF4A, MafA and insulin). Finally, functional analyses were carried out to examine the secretion of functional proteins, such as dopamine and insulin from the differentiated cells. In this study, the isolated rat full-term AFSCs not only possessed similar expression profiles as highly potent stem cells, but also exhibited a wide differentiation capability in generating not only the derivatives of the three primary germ lineages but also the functional ones. This strongly suggests AF of full-term pregnancy as a great potential source of stem cells with therapeutic value and opens the opportunity towards the establishment of full-term AFSCs in human counterpart as a potential candidate cells to treat various degenerative defects.